PENGARUH SOFT SKILL DAN HARD SKILL TERHADAP KESIAPAN KERJA LULUSAN SMA NEGERI 3 KOTA JAMBI DI MASA PANDEMI COVID 19 - Setiawati, Desi; Mayasari, Mayasari (SJEE (Scientific Journals of Economic Education), 2021)
Abstract This study aims to determine (1) the effect of soft skills on writing work readiness of SMA Negeri 3 Jambi City. (2) The effect of hard skills on job readiness of graduates of SMA Negeri 3 Jambi City. (3) The influence of Soft Skills and Hard Skills on job readiness of SMA Negeri 3 Jambi City graduates.This research design uses survey research methods, with data collection techniques through observation, questionnaires. Where the population in this study were 133 students with a sample of 57 students. The data processing techniques in this study are the Research Instrument Validity Test, Research Instrument Reliability Test, Quantitative Descriptive Analysis, Normality Test, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test, Multiple Regression Test, Hypothesis Test, Partial Test (t) and Simultaneous Test ( F). Keywords: Soft Skill, Hard Skill, Work Readiness.